(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
India is a fast developing country, due to increasing urbanization there is huge demand for construction of structures and also the demolition old ones. In earlier study, a sustainable construction materials (bricks) using construction and demolition waste are developed. Cement and fly ash are used as binder and C D waste is used as fine aggregate. The amount of C D waste generated in the country has increased considerably in recent years due to rapid pace of development. There is no uniform and systematic process followed in determining the total quantity of C D waste generated or in collection, transportation and disposal of C D waste anywhere in India. This study investigates the bricks characteristics, both strength and aesthetic tests such as water absorption test, compressive test are to be conducted on bricks using construction waste and normal bricks which are to be compared. This project is very useful as it is eco-friendly to the environment.